Malaysia's implementation of the multilateral system of access and benefit-sharing - Nijar, Gurdial Singh; Bioversity International; Malaysian Agricultural Research Development Institute (2012)
This study examines a number of issues related to Malaysia’s implementation of the multilateral system of access and benefit-sharing created by the International Treaty on Plant Genetic Resources for Food and Agriculture. The paper suggests a three-stage approach to addressing these issues. First, it establishes a process for ascertaining which of Malaysia’s plant genetic resources for food and agriculture are under government management and control. It includes a survey of the major institutions in Malaysia holding collections of crops and forages, and examines whether they function as an extension of a government department. If so, the paper argues that the plant genetic resources held by those organizations and listed in Annex 1 of the Treaty are automatically included in the Treaty’s multilateral system (if they are also in the public domain, as the Treaty stipulates). Second, the paper examines existing laws to ascertain whether they include provisions for implementing the multilateral system. The study suggests that it is possible to implement the multilateral system in Malaysia without the time-consuming process of enacting a new law, or even amending existing laws. While such initiatives are not necessary however, there may be situations in which amending existing statues would contribute to long-term legal certainty. The paper offers draft text for such amendments. Finally, the study examines a national law on access and benefit-sharing made pursuant to the Convention on Biological Diversity and recommends that it exclude the PGRFA in the multilateral system from its ambit, thereby creating legal and policy space for implementing the multilateral system.